PlantGENE report on panel discussion: advancing plant biotechnology in Africa - Malzahn, A.A.; Songstad, N.; Tripathi, L.; Okwuonu, I.; Sithole-Niang, I.; Runo, S.; Wagaba, H.; Houassi, M.; Kaeppler, H.; Gordon-Kamm, W.; Lee, K.; Parrott, W.; et al. (2025)
This report provides an overview of the content and data collected from the “Successes, Challenges, and Opportunities Plant Transformation Research in Africa” panel discussion. Organized by PlantGENE, this event brought together scientists and stakeholders across the globe to examine the complex challenges and emerging opportunities in plant transformation research in laboratories across Africa. The discussion, rooted in insights from a panel of six leading scientists, highlights critical issues including restrictive regulatory environments, prohibitive costs, and the inconsistent availability of essential research materials. Additionally, the pervasive “brain drain” phenomenon, where skilled researchers leave the continent for better opportunities, exacerbates the difficulties faced by African scientists. Despite these challenges, the report also identifies significant advancements, particularly in the growing recognition of African leadership within universities and national agricultural research systems (NARS). These institutions, supported by highly skilled faculty and motivated graduate students, are producing high-quality research that contributes to global scientific knowledge. The panelists emphasized the necessity of creating an environment that encourages African scientists to remain on the continent and address local challenges through innovative research. Strengthening intra-African networks and fostering collaborations with the global scientific community are proposed as essential strategies to achieve this. This report underscores the critical need for substantial investments from both global and African organizations, working with African governments, to support these efforts. Furthermore, it calls for science-based decision-making and fair regulatory frameworks to align with unique opportunities and risks associated with technological advancements in Africa. This paper details the observations of six panelists and analyzes the results of attendee surveys in order to document these challenges and opportunities while advocating for sustained investment and strategic partnerships to build a thriving bioeconomy across Africa.